1958
DOI: 10.1139/o58-024
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cold Acclimation on the Size of Organs and Tissues of the Rat, With Special Reference to Modes of Expression of Results

Abstract: In experiments in which two groups of animals of different mean body weight are compared, individual organ weights of the animals can be expressed as absolute weights, as fractional weights, or as absolute weights statistically regressed onto constant body weights. The second, and commonest, mode of expression involves the assumption that the part is directly proportional to the whole, and this is shown to be unlikely for all organs except the muscle mass. Practical as well as theoretical justifications for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
2

Year Published

1961
1961
1996
1996

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(24 citation statements)
references
References 4 publications
4
18
2
Order By: Relevance
“…In contrast to the findings of Heroux (1963), there was a significant increase in the amount of fur after a comparatively short period in the cold. Barnett, Coleman & Manly (1959) found that mice kept and bred for many generations at -3' had relatively more fur than those kept and bred at ZIO, but they made no measurements over short periods.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the findings of Heroux (1963), there was a significant increase in the amount of fur after a comparatively short period in the cold. Barnett, Coleman & Manly (1959) found that mice kept and bred for many generations at -3' had relatively more fur than those kept and bred at ZIO, but they made no measurements over short periods.…”
Section: Discussioncontrasting
confidence: 99%
“…The animals having the stock diet at 5' did not eat quite enough extra food to enable them to grow at the same rate as animals having the stock diet at 2 1 O , whichagrces with the findings of Heroux (1961Heroux ( , 1963. The animals having the low-protein diet and kept at Z I O lost weight but, in contrast to the findings of Andik et al (1963), none of them died during the 9 weeks of the experiment.…”
Section: Discussionsupporting
confidence: 78%
“…This observation differs from previous work showing increased mucosal wet weight, villous height and crypt cell production rate in the small bowel of cold-acclimatised rats Sagor et al, 1982;Heroux & Gridgeman, 1958;. In these studies, however, animals were housed at lower temperatures (5-60C) small bowel.…”
Section: Discussioncontrasting
confidence: 72%
“…Changes of this type probably reflect a temporary redistribution of blood concomitant with the disturbed hemostatic mechanisms. It could be that these changes relate to the hypertrophy of these organs during cold acclimation which has been reported for the rat by Heroux and Gridgeman (1957). Page and Babineau (19 53) have also reported a hypertrophy of the liver and kidneys of rats during prolonged exposure to cold.…”
Section: Gans (Everett and Simmons 1958)mentioning
confidence: 66%